Using Electronic Works And Discourse Analysis In Literature Lessons - Muhayyo Egamberdiyevna, Inoyatova; Xilolaxon Maxmutovna Тоjiboyeva; Alikulovna, Yuldosheva Maxmuda; Mirjamolovna, Oymatova Nilufar (Journal of Neonatal Surgery, 2025)
The article discusses the urgent problem of using electronic developments based on the discourse analysis methodology in literature lessons for grades 5-6, the scientific apparatus of this problem, methodology, content of the discourse analysis methodology, intellectual quest, study and analysis of the language of a writer or literary hero, debate, improving the quality of literature education through the use of game technologies, analysis of scientific, pedagogical and methodological literature on this problem, reliance on innovative and active principles through the use of IT technology in literature lessons for grades 5-6, development of creative activity skills in students, presentations suitable for literature for grades 5-6, video and audio tools, programmed test tasks for controlling students' knowledge, recommendations for teachers on the appropriate use of software, research results and conclusions.